Challenges in Developing Arabic Language Competence Among Madrasah Aliyah Students: Educator and Graduate Perspectives - Amalia Fahrunnisa; Gita Rahmatika; Imam Imam (Gunung Djati Conference Series, 2026)
This study aims to identify educators’ views on the level of Arabic language competence among Madrasah Aliyah students, the main challenges faced by teachers in developing Arabic proficiency within the madrasah environment, graduates’ perceptions of the relevance and effectiveness of the Arabic learning they received, and the strategies that can be developed to address these challenges based on the perspectives of both educators and alumni. This research employs a descriptive qualitative approach to understand the challenges of developing Arabic language competence in Madrasah Aliyah from the viewpoints of teachers and graduates. Primary data were obtained from teachers and alumni through in-depth interviews, classroom observations, and documentation, while secondary data were derived from institutional documents and relevant literature. Data were analyzed using the Miles and Huberman interactive model, data reduction, data display, and conclusion drawing, allowing the findings to provide a comprehensive picture of the realities of Arabic language learning in the madrasah context. The results indicate that students’ Arabic competence, particularly in productive skills, remains low due to traditional teaching methods, limited facilities, and a lack of supportive language environments. Teachers face challenges such as low student motivation, disparities in students’ foundational abilities, and limited opportunities for professional development. Graduates perceive the Arabic learning they received as insufficiently aligned with current curricular and real-world demands. Improvement strategies point toward the adoption of communicative approaches, the integration of TPACK-based technology, and reforms in curriculum and learning materials.